The Contested and Expanding Meaning of Democracy - Asafa Jalata (Journal of Interdisciplinary Sciences)
The meaning of democracy has been contested, limited or expanded because it has been culturally situated and changed with changing historical and politico-economic conditions. Historically speaking, democracy can be hierarchical, exploitative and exclusive or egalitarian and inclusive depending on a specific social system. In most cases, the privileges of democracy were not equally shared within a population group or among different peoples, and what was democracy for one group could be slavery, stratification of class and gender, exclusion, oppression, colonialism and dictatorship for others. Starting from ancient times, certain peoples such as Athenians, which were culturally and geographical connected in a limited geographical space began to practice forms of democracy. Such people had the challenge of working with culturally, economically and geographically diverse populations on the principles of democracy, equality, and equity. However, people like the Oromo of Northeast Africa had democracy known as the gadaa system and its subset female institution known as siiqqee and overcame most of these problems through horizontal organization and specific social democratic policies. Some scholars recognize that the meaning of democracy expands when a people within and without a given political community struggle for further expansion of political, economic, and social rights and freedoms. The historical experiences of various democratic societies show that democratic conditions emerged because of internal or/and external political pressures. The paper addresses three major issues: First, it examines the cases of Athenian and Oromo democracies and explains their historical and cultural roots, essence, characteristics and principles. Second, the piece explains why the issue of democracy is open and contested. Third, it illustrates how the meaning of democracy can be limited based on certain sociocultural conditions or how it can expand through struggles, theoretical and practical knowledge, ideological innovations, and institutional and organizational transformations.